Development of Problem Based Learning Oriented Student Worksheets in Improving Students' Critical Thinking Skills - Bunga Dara Amin; S Salmiah Sari; Nurhaedah Ahmadiah (Postgraduate, University of Mataram, 2023)
This research is a research on the development of Problem Based Learning oriented student worksheets to improve the critical thinking skills of class X MIPA students of SMAN 22 Makassar. This study aims to describe the feasibility of PBL-oriented students' worksheet teaching materials, practitioners' assessment of PBL-oriented, the effectiveness of PBL-oriented Student Worksheets in learning physics. The subjects of this research trial were 38 class X MIPA students at SMAN 22 Makassar and 10 students were tested on the Physics Teacher Consultation Community. The type of research used is the research and development method. Research on the development of student worksheets is oriented towards using the 4D model which consists of define, design, develop, and disseminate. The instruments used in this study were teaching material validation sheets, practitioner response questionnaires and students' critical thinking skills test instruments. The eligibility criteria for learning media are seen from the aspect of its validity. The practicality criterion is seen from the practitioner's assessment of the teaching materials, and the effectiveness criterion is seen from the increase in students' critical thinking skills test results. Based on the results of the analysis, the following conclusions were obtained: (1) the teaching materials in the form of PBL-oriented student worksheets which were developed, based on expert judgment using Aiken V index analysis, were declared valid and suitable for use with minor revisions; (2) teaching materials in the form of PBL-oriented student worksheets in terms of the response of physics teacher practitioners are in the very good category; (3) the effectiveness of teaching materials in the form of PBL-oriented student worksheets seen from the ability of students' understanding of concepts analyzed by N-gain obtained an average value of 0.51 in the medium category which means that there is an increase in students' critical thinking skills so that it can be said that the teaching materials in the form of PBL-oriented student worksheets which were developed were effective in increasing students' conceptual understanding abilities.